Children of a (Policy) Revolution: The Introduction of Universal Child Care and Its Effect on Fertility. Issue 5 (26th November 2015) - Bauernschuster, Stefan; Hener, Timo; Rainer, Helmut
Abstract: What role does affordable and widely available public child care play for fertility? We exploit a major German reform generating large temporal and spatial variation in child care coverage for children under the age of three. Our precise and robust estimates on birth register data reveal that increases in public child care have significant positive effects on fertility. The fertility effects are more pronounced at the intensive than at the extensive margin, and are not driven by changes in the timing of births or selective migration. Our findings inform policy makers concerned about low fertility by suggesting that universal early child care holds the promise of being an effective means of increasing birth rates.